Zebra finch song is a very short-range signal in the wild: evidence from an integrated approach. (22nd September 2021) - Loning, Hugo; Griffith, Simon C; Naguib, Marc
Abstract: Birdsong is typically seen as a long-range signal functioning in mate attraction and territory defense. Among birds, the zebra finch is the prime model organism in bioacoustics, yet almost exclusively studied in the lab. In the wild, however, zebra finch song differs strikingly from songbirds commonly studied in the wild as zebra finch males sing most after mating and in the absence of territoriality. Using data from the wild, we here provide an ecological context for a wealth of laboratory studies. By integrating calibrated sound recordings, sound transmission experiments and social ecology of zebra finches in the wild with insights from hearing physiology we show that wild zebra finch song is a very short-range signal with an audible range of about nine meters and that even the louder distance calls do not carry much farther (up to about fourteen meters). These integrated findings provide an ecological context for the interpretation of laboratory studies of this species and indicate that the vocal communication distance of the main laboratory species for avian acoustics contrasts strikingly with songbirds that use their song as a long-range advertisement signal. Abstract : In their natural environment, zebra finches sing softly and their songs do not transmit far. This finding is in sharp contrast with our current understanding of birdsong as a typical form of long-range communication. Since the zebra finch is the main laboratory model for bird acoustics, our findings from zebra finches in the wild combined with data on hearing physiology provide a new ecological perspective on the potential function of zebra finch song.